Virtual Reality Program for Enhancing Learning in a High School Human Biology Course (Proceedings of the International Conference on Future of Education, 2021)
The creation of virtual environments and their implementation have been a matter ofgreatest importance in the last decades, becoming a breaking point for progress in different fieldslike communication, entertainment, and education. Additionally, the learning and teaching ofhuman biology have been more relevant through the increase of biology-related research andmedical advances. However, learning human biology, especially anatomy, is perceived asdifficult by students. The objective of this study is to improve the learning of human biology byimplementing a Virtual Reality Program (VRP) in a high school human biology course,measuring academic performance in a final knowledge evaluation. The VRP used immersiveVirtual Reality (VR) devices (Oculus-Go® and Oculus-Rift®) and consisted of three stages:exploration, virtual reality lab, and knowledge reinforcement. In the exploration, the students hada guided approach of the topics with a professor’s explanation; afterward, they had guided andindependent collaborative experience in the Virtual Reality lab; and finally, their knowledge wasreinforced in communication with the professor. A post-test only with a control group design wasemployed with 120 students. There were two experimental groups (63 students) and two controlgroups (57 students). After completing the stages of the VRP, all the groups had a finalknowledge evaluation where the experimental groups obtained a mean of 77.24, while the controlgroups had 69.11. There was a significant statistical difference between the groups with a P
Keywords: educational innovation; virtual reality; active learning; academic performance